Signals : News bulletin of Signals London - Medalla, David; Keeler, Paul (Londen : Signals Gallery, 1964)
Signals was a periodical that was published in association with the London-based contemporary art gallery Signals (1964-66) in ten newspaper-sized issues, with the third number being a double issue making a total of 11 published altogether.(http://artistsperiodicals.blogspot.com/2018/12/signals.html)
Http://artistsperiodicals.blogspot.com/2018/12/signals.html
Engels
Tijdschriften
Keywords: Signals Gallery (Londen, 1964-1966).